2000
DOI: 10.1046/j.1365-2125.2000.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones in man: their effects on resting vascular tone, angiotensin converting enzyme activity and angiotensin II‐induced vasoconstriction

Abstract: Aims Oestrogens in women have been shown to cause vasodilation which may re¯ect alterations in the activity of vascular angiotensin converting enzyme (ACE) and/or sensitivity to angiotensin II. The aim of this study was to assess the effect of ovarian hormones on vascular tone, vascular ACE activity and vasoconstriction to angiotensin II in males. Methods Eight volunteers were randomised in a crossover design to oestradiol, medroxy-progesterone, and placebo. Vasoconstriction to angiotensin I and angiotensin II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In denuded rat aortic rings, there is no sex difference in E 2 -induced vasodilation (9), and E 2 -induced vasorelaxation is independent of sex in rat tail arteries (10). Effects of E 2 on vascular reactivity are also evident in human males, as clinical studies show an improvement in blood flow following infusion of conjugated equine estrogens or oral E 2 (2,17). Although males used in the current study were gonad intact, castration has no effect on the vasodilatory response to E 2 in rat aortic strips and tail arteries (6,10).…”
Section: Discussionmentioning
confidence: 83%
“…In denuded rat aortic rings, there is no sex difference in E 2 -induced vasodilation (9), and E 2 -induced vasorelaxation is independent of sex in rat tail arteries (10). Effects of E 2 on vascular reactivity are also evident in human males, as clinical studies show an improvement in blood flow following infusion of conjugated equine estrogens or oral E 2 (2,17). Although males used in the current study were gonad intact, castration has no effect on the vasodilatory response to E 2 in rat aortic strips and tail arteries (6,10).…”
Section: Discussionmentioning
confidence: 83%
“…Another factor to be determined is the minimum time necessary for changes in ACE activity to be apparent following commencement of HRT. An acute effect is unlikely because treatment of men within 24 h prior to study with either oral oestradiol valerate or medroxyprogesterone acetate was not seen to influence plasma ACE activity (Lee et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that vaginal implants of progesterone in non-pregnant ovariectomized sheep increased nitric oxide synthase expression in the endothelium of the uterine artery but not in that of the omental, renal or mammary arteries [2], and that progesterone relaxes pre-contracted segments of small saphenous artery of the rat [3]. Also, it has been reported in humans that acute intra-arterial progesterone did not significantly affect forearm blood flow, particularly that mediated by endothelial mechanisms [4, 5], and that progesterone applied as a vaginal cream decreased forearm blood flow [6]. …”
Section: Introductionmentioning
confidence: 99%